The Influence of Social Comparison Orientation on Attitudinal Loyalty, Brand Happiness, and Willingness to Purchase a Masstige Brand - Rachman Tri Fridian; Burhanudin Burhanudin (Jurnal Manajemen dan Kewirausahaan, 2023)
Individuals often compare themselves to others because of the rise of social media, which can make them want to buy something like a luxury brand. However, reaching luxury brand will be difficult because in addition to the high price, the product is also made in limited quantities. Therefore, masstige brand is an alternative that companies can use. This study aims to determine the effect of social comparison orientation on willingness to purchase masstige brands and their impact on attitudinal loyalty and brand happiness. In this study, there were 211 participants. Structured equation modeling was used to analyze data. The results of analysis show social comparison orientation has an impact on willingness to purchase a masstige brand, resulting in attitudinal loyalty and brand happiness.